Pemarkah Persona Bahasa Gebe Halmahera Tengah - Ety Duwila; Nurain Jalaludin (TEKSTUAL, 2022)
This research intends to describe the markers of personal pronouns in Gebe. As an ethnic language, Gebe language has its own uniqueness. Gebe language has a grammatical sophistication that is different from other languages. There are basic patterns that can be explained. However, not all of the basic patterns of the Gebe language will be explained in this research because the scope of linguistic studies covers many things. To overcome this broarness, the study only observes and describes the personal pronoun markers which are one of the unique characteristics of the Gebe language. The method used in this research is descriptive qualitative. This approach is chosen because it relates to the purpose of this study, which is to show the form of personal pronouns in Gebe language. The results show that in the Gebe language there, are personal pronouns ane, amne, itne, awya, mewya, yes, and sia. Meanwhile, the personal pronoun markers in Gebeese are y-, k-, t-, m-, f-, n-, and d-.